2020
DOI: 10.2147/opth.s275977
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trends in Real-World Neovascular AMD Treatment Outcomes in the UK</p>

Abstract: Purpose: To report trends in real-world outcomes of anti-vascular endothelial growth factor (anti-VEGF) therapy for neovascular age-related macular degeneration (nAMD) in the United Kingdom (UK) over the last decade. Design: Systematic review. Methods: Medline, PubMed, and Embase databases were searched from 9 April 2010 to 8 April 2020 for publications that met the inclusion criteria: treatment-naïve eyes, UK-only data and ≥1 year of follow-up. ICHOM (International Consortium for Health Outcome Measures) outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 76 publications
3
24
0
1
Order By: Relevance
“…The number of injections reported in our study differed significantly from the average amount of injections reported in clinical trials. However, our findings are in line with a previously published real-life study by Gayadine-Harricham et al and with a review by Metha et al showing huge variability of this parameter in previous studies ranging from 4.5 to 11.4 injections during the first year of treatment [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The number of injections reported in our study differed significantly from the average amount of injections reported in clinical trials. However, our findings are in line with a previously published real-life study by Gayadine-Harricham et al and with a review by Metha et al showing huge variability of this parameter in previous studies ranging from 4.5 to 11.4 injections during the first year of treatment [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Our visual outcomes are concordant with those from Mehta et al study, which reviewed 26 studies providing outcome data on Ranibizumab and Aflibercept. They found that the visual gains achieved in the first year of treatment were rarely maintained, and suggested that under-treatment was likely a contributing factor [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to a few reasons. First, the wide administration of anti-VEGF agents [ 18 , 19 ]. The emergence of anti-VEGF agents has revolutionized the treatment strategies against neovascular AMD, which can dramatically improve and prolong visual function, leading to alleviation of the AMD global burden.…”
Section: Discussionmentioning
confidence: 99%
“…At that time, it was observed that real-world data did not always reflect smooth results from registration studies. After several years of treatment, the mean visual acuity (VA) had nevertheless improved as compared with presentation, in spite of frequency of delivered injections being actually inferior to that reported in the literature [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 87%